Should the Rules for Interim Reporting in Hong Kong Be Changed? A Review of Annual Reports - Miller, Gary A (The International Journal of Accounting and Business Society, 1996)
The purpose of this research was to investigate the need forchanges in the requirement for interim reporting in Hong Kong. In order to partily fulfill the purpose, date was gathered from Hong Kong annual report. Many countries aready require interim reporting but the reporting details vary from country to country. At the present, companies in Hong Kong report on a semi-annual basis, but these reports are not officially reviewed. Also only limited information is provided. Some have argued this situation should also change. Only very limite information is Hong Kong interim reports at the present time. Changes my need to be made or Hong Kong may not remain competitive in international financial markets. International financial markets are rapidly becoming a single global market. For these markets, most large institutional users are not satisfied with the existing levels of disclosures by multination firms. These issues will remain important to those interested in Hong Kong markets. It is hoped that this study has provided some helpful information about the interim reporting practices in Hong Kong and provide some insight as the direction future research should take. Keywords: interim financial statements, financial statement reviews